Crinum latifolium L. var. crilae Tram & Khanh, var. n. - A new variety of the species Crinum latifolium L. (Amaryllidaceae) in Vietnam - Ngoc Tram, Nguyen Thi; Khanh, Tran Cong (Academia Journal of Biology, 2012)
Nguyen Thi Ngoc Tram et al. has investigated of C. latifolium L. population that is existed in Vietnam and discovered a specific plant sample contents a number of chemical components, which are differed from the other plants of the Crinum’s population in Vietnam. In combination with the botanic characters, this shows clearly that the plant sample of C. latifolium L. is a new variety of this species. It is named “Trinh nu crila” - Crinum latifolium L. var. crilae Tram & Khanh, var. n. Crinum latifolium L. var. crilae Tram & Khanh, var. n.: Perennial herb to 30-40 cm tall. Bulbous sub-globose, 9-12 cm in diameter. Leaves linear, fleshy, 40-50(-90) cm long, 4-6(-10) cm wide, margins entire and undulate, shining green, both side of basal leaf colorless, sheathed. Inflorescences umbellate in terminal with two spathaceous triangular bracts, 5-7 cm long, bottom 2.5-3 cm wide, scape solid, about 40-50 cm long, tangent surface 1 × 1.5 cm. Flower buds fusiform, 10-11 cm long, 3.5 cm wide. Flowers 6-8, nearly sessile, large, funnel-shaped, white with pink; sepals and petals similar in form, acuminate; outside of sepal with long spot in the middle colored pale purple red; outside of petals spotted along purple red, about 1/3 in width; perianth-tube 7-8 cm long, 5-6 mm in diameter, slightly curved. Stamens 6, inserted in the throat of perianth, filaments linear, slender and curved, 7-8 cm long; anthers dorsifixed, 1-2 cm long. Ovary inferior, obovoid-cylindrical, 10-15 mm long, 7-8 mm wide, style filiform, slender, 19-20 cm long, upon part purple red, stigma entire. Fruit subglobose. Flow.: June - August.